Literatur Review: The Relationship Between Macronutrient Intake and Sleep Duration and the Occurrence of Menstrual Disorders in Women of Reproductive Age - Zul Fajri; M. Hamsah; Andi Kartini Eka Yanti; Asrini Safitri; Gina Isni Djanuaresty Iskandar (Journal of Asian-african Focus in Health, 2026)
This literature review examines the relationship between macronutrient intake and sleep duration with the incidence of menstrual disorders in women of reproductive age. Based on a systematic analysis of ten selected scientific studies, the findings indicate that carbohydrate intake is significantly associated with menstrual disorders, particularly when high glycemic index foods and excessive added sugars are consumed, leading to hormonal imbalances through insulin dysregulation. Protein intake also shows a significant relationship, where both deficiency and excessive consumption of animal protein may disrupt ovulation, while plant-based protein demonstrates a protective effect. Fat intake, especially high saturated fat consumption, is linked to increased severity of dysmenorrhea and premenstrual syndrome (PMS), whereas omega-3 fatty acids contribute to symptom relief. In addition, insufficient sleep duration (less than 7 hours per day) significantly increases the risk of menstrual irregularities and pain intensity. Biologically, these relationships are explained through multiple mechanisms, including disruption of the hypothalamic-pituitary-ovarian (HPO) axis, insulin resistance, increased prostaglandin production, and the reciprocal interaction between poor diet and inadequate sleep. Despite strong evidence, significant research gaps remain, particularly the lack of experimental or clinical studies examining the combined effects of dietary and sleep interventions on menstrual health. Therefore, a comprehensive approach integrating nutritional and lifestyle modifications is essential in managing menstrual disorders.